(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2016)
Taking into account the equivalent principle of Einstein and the special relativity equations, we infered, for a flat space time, a new formulae of gravitation. We assume two reference frames, one of these at rest, in the center of gravitatiuonal field, and another one, corresponding to the field itselft. If the gravitational field is an inverse square law, the rest frame field results a modified newtonian force. We applicate the same procedure to the electrical field and results a weak force comparable with gravitation strength. The proportional constant must be the gravitational constant. We calculate the gravitatiobal constant using the value of the electrical constant and the parameter of the electron, and we found a close value with the expererimental results sugesting the the gravitation is a residual product of the electricity.